2015
DOI: 10.1039/c5nj00318k
|View full text |Cite
|
Sign up to set email alerts
|

Dithionite and sulfinate complexes from the reaction of SO2with decamethylsamarocene

Abstract: 2 ] (2), was obtained as the second major product after workup of the filtrate. Additionally, the dithionite complex [{(Z 5 -C 5 Me 5 ) 2 Sm} 2 (S 2 O 4 )] (3) and the sulfinate complex [{(Z 5 -C 5 Me 5 )Sm} 2 (C 5 Me 5 SO 2 ) 4 ] (4) were isolated as minor products. All compounds were characterized by single crystal X-ray diffraction. As major reaction pathways, the reductive coupling of two SO 2 molecules to form the dithionite anion S 2 O 4 2À and the nucleophilic attack of one samarocene C 5 Me 5 ligand on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
(61 reference statements)
0
18
0
Order By: Relevance
“…The cation of compound 5 also contains six bridging tolylsulfinate TolSO 2 groups, in which the S–O distances are averaged and fall into the range of 1.53 ± 0.01 Å. In general, the geometry of the tolylsulfinate groups is in excellent agreement with that of other sulfinate complexes [Zn­(O 2 SC 5 Me 5 ) 2 (tmeda)], the reaction product of [(C 5 Me 5 ) 2 Yb­(THF) 2 ] with SO 2 , [{(η 5 -C 5 Me 5 ) 2 Sm­(C 5 Me 5 SO 2 )} 2 ], and the β-diketoiminate complex [((ArNC­(CH 3 )­CH­(CH 3 )­CNAr)­Zn­(O­(SO)­Et)] (Ar = 2,6-diisopropylphenyl) . However, such groups are somewhat different from those in the reaction product of digallane with SO 2 , where the S–O distances clearly differ [S(1)–O(2) 1.491(2) Å; S(1)–O(1) 1.550(2) Å] …”
Section: Results and Discussionmentioning
confidence: 58%
“…The cation of compound 5 also contains six bridging tolylsulfinate TolSO 2 groups, in which the S–O distances are averaged and fall into the range of 1.53 ± 0.01 Å. In general, the geometry of the tolylsulfinate groups is in excellent agreement with that of other sulfinate complexes [Zn­(O 2 SC 5 Me 5 ) 2 (tmeda)], the reaction product of [(C 5 Me 5 ) 2 Yb­(THF) 2 ] with SO 2 , [{(η 5 -C 5 Me 5 ) 2 Sm­(C 5 Me 5 SO 2 )} 2 ], and the β-diketoiminate complex [((ArNC­(CH 3 )­CH­(CH 3 )­CNAr)­Zn­(O­(SO)­Et)] (Ar = 2,6-diisopropylphenyl) . However, such groups are somewhat different from those in the reaction product of digallane with SO 2 , where the S–O distances clearly differ [S(1)–O(2) 1.491(2) Å; S(1)–O(1) 1.550(2) Å] …”
Section: Results and Discussionmentioning
confidence: 58%
“…Looking for the substrate that could act as three-atom bracket for Ga–Ga bond, we turned to sulfur dioxide, which serves well as a ligand for transition-metal ions and demonstrates a number of coordinating modes. However, s-, p-, and f-element coordination chemistry of sulfur dioxide is limited by few dithionite derivatives. We found that treatment of digallane 1 with 2 equiv of SO 2 in hexane at ambient temperature results in an immediate color change from deep blue to red, which is indicative for the formation of dpp-Bian radical anion. The dark red (dpp-Bian)­Ga­(O 2 S–SO 2 )­Ga­(dpp-Bian) ( 5 ; Scheme ) precipitates from the reaction mixture within few minutes.…”
Section: Resultsmentioning
confidence: 99%
“…17,18 Recent reports concerning the activation of SO 2 include uranium(III) compounds, which allow for the formation of sulfite and dithionite complexes 19 as well as the reaction of SO 2 and decamethylmetallocenes. 20,21 Herein, we report on an unusual binding mode of SO 2 triggered by metal−ligand cooperation (MLC), where both the transition metal center and a iminopyridine-based C-nucleophilic actor ligand participate in the activation of SO 2 via M−O and C−S bond formation (Scheme 1, (III)). MLC in transition metal complexes involving pyridine-based ligands was developed into an important tool in bond-activation chemistry.…”
mentioning
confidence: 79%
“…Specifically, SO 2 can act as an ambiphilic ligand: The η 1 - S coordination mode to a metal center can be governed by electron donor (L-type) or electron acceptor (Z-type ligand) properties through the same sulfur atom. Each scenario is characterized by a distinct geometry, that is, a coplanar or pyramidal arrangement, respectively (Scheme , (I) A,B). , In addition, the η 1 - O (C) , and η 2 - S,O coordination modes are observed (D). Stephan, Erker, Grimm, and co-workers reported the activation of SO 2 by frustrated Lewis acid/base pairs (FLPs) under concomitant P–S and B–O bond formation (Scheme , (II)). , Recent reports concerning the activation of SO 2 include uranium­(III) compounds, which allow for the formation of sulfite and dithionite complexes as well as the reaction of SO 2 and decamethylmetallocenes. , Herein, we report on an unusual binding mode of SO 2 triggered by metal–ligand cooperation (MLC), where both the transition metal center and a iminopyridine-based C-nucleophilic actor ligand participate in the activation of SO 2 via M–O and C–S bond formation (Scheme , (III)). MLC in transition metal complexes involving pyridine-based ligands was developed into an important tool in bond-activation chemistry. Along these lines, we recently described an anionic Re­(I) triscarbonyl complex, which includes a redox active bidentate amidopyridine ligand (K­[Re­( amidopy )­(CO) 3 ] (Scheme , 1 ).…”
mentioning
confidence: 99%